Wild creations : inspiring projects to create plus plant care tips & styling ideas for your own wild interior - Carter, Hilton, 1979- (CICO Books, 2021)
Carter, the Instagram star of the plant world and creator of green interiors has given us glimpses into many stunning plant-filled homes where ivy and creeping figs hang miraculously from ceilings, moss and ferns grow effortlessly to create living walls, fiddle leaf ferns and cheese plants thrive, whilst air plants beautify artworks and succulents flourish whether in pots on windowsills or planted in terrariums. Now in his third book, Wild Creations, Hilton actually shows you how you can create these amazing fixtures that enable plants to become such an integral part of an interior. Divided into two sections, My Plant DIY and My Plant Hacks, Wild Creations shows you step by step how you can create hanging rails, moss walls, vegan leather pot holders, terrariums and many more stunning projects that will give you the green interior you crave. And just so your plants feel at home in your interior there is even a painting by numbers jungle mural, plus plant-scented candles to make sure your interior not only stays wild but that you and all its inhabitants thrive from the health giving benefits of greenery.